PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PELECEHAN SEKSUAL PADA ANAK DI KEPOLISIAN RESOR ROKAN HILIR - Caryn, Caryn; Effendi, Erdianto; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Article 76 E of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection states that the criminal act of sexual abuse against a child which is punishable with a minimum sentence of 5 (five) years in prison cannot be mediated due to the threat of the shortest sentence. 5 (five) years imprisonment is a category of serious criminal offense, but in reality at the Rokan Hilir Police, there are several cases of sexual immorality that have not been resolved because the police have suspended their investigations due to mediation. In this case, it can be said that the law enforcement carried out by the Rokan Hilir Police has not been maximized so that it does not provide a deterrent effect on the perpetrators and the community who commit criminal acts of sexual abuse against children.This type of research is sociological legal research, namely as an attempt to see the effect of the enactment of positive law on people's lives. This research is also descriptive in nature, namely the author tries to describe law as a social control related to the formation and maintenance of social rules, with a basis that the legal ability to control human behavior and create a conformity in these behaviors.This study aims to determine how law enforcement is carried out by the Rokan Hilir Police, especially the Women and Children Protection Unit Investigators, what obstacles are faced in law enforcement and what efforts can be made to overcome law enforcement obstacles at the Rokan Hilir Police Resort.The results of this study are to explain that the law enforcement carried out by the Rokan Hilir Police, especially the Women and Children Protection Unit Investigators, has not been maximal in cases of sexual abuse against children. The obstacles faced by the police are the lack of quality and quantity of the Women and Children Unit Investigators, the lack of cooperation between victims or victims' families in providing information related to cases being processed, and lack of community legal awareness. The efforts that the authors offer in this study are to improve the quality and quantity of investigators for the women and children unit at the Rokan Hilir Police, increasing public insight regarding the importance of legal awareness in order to create justice, benefit and general welfare.Key Words : Law Enforcement - Crime - Sexual Harassment – Children